Recycling local waste into useful resource - Lai, Yi Ling (2017)
Despite large efforts to boost recycling, the amount of waste generated still increased tremendously over the years. As such, more efficient methods were employed to recycle waste to reduce the strain on the only waste landfill in Singapore. With a predicted lifespan of 20 more years, the need to explore more innovative ways to recycle Incineration Bottom Ash (IBA) which is disposed into the landfill becomes essential. Recycling of IBA is widely used in cement production and construction of roads in many countries. Yet, these efforts may be insufficient. Hence, new creative usages of IBA in Singapore, such as extraction of metal content from IBA and using it as a source of land reclamation are exploited. Potentially, there may be more useful purposes of IBA. Thus, further research can be done to utilize IBA more effectively. This report proposes the use of IBA in Autoclaved Aerated Concrete (AAC). The aluminium, lime and coal fly ash contents in the original mix design of AAC were replaced with IBA containing high aluminium (IBA >6.3mm non-ferrous), calcium (IBA <300µm) and silicon (IBA glass) content respectively. Their pore structure, density, rising height and compressive strength were then determined. Comparing these properties, the most cost-efficient IBA AAC was then established. As such, this report aims to look at how IBA can be utilize more efficiently, thereby increasing the lifespan of the landfill and simultaneously reduce the cost of original AAC.